Deconstructive Adaptation on Differentiated Instruction Model as a Manifestation of Independent Learning - Abdul Azis; Syakir Syakir; Karta Jayadi; Wandah Wibawanto (International Conference on Science, Education, and Technology, 2023)
Deconstruction is viewed as a new and radical perspective in understanding texts or current events and has broad and challenging implications for changing perspectives in education and educational management, aiming to enhance stronger critical and creative thinking skills for participants. Learner-centered education has become an open trend in contemporary education in Indonesia, particularly in the digital-based social, era 5.0. The adaptation of deconstruction in differentiated learning model presents both opportunities and challenges in developing critical and creative thinking, fostering collaboration, and strengthening communication skills while also considering the needs of individual learners. This study examines and analyzes the adaptation of deconstruction to the differentiated learning model as a manifestation of independent learning. It employs a radical hermeneutic qualitative research approach, conducting an in-depth literature review on the various forms of deconstruction adaptation that can be applied in differentiated learning. The adaptation of deconstruction allows educators not only to address the diverse needs of individual learners but also opens up greater opportunities to build critical and creative thinking, collaboration, communication skills. Learners become individuals with strong and sharp critical thinking skills who continuously offer new ideas and concepts in response to changes and events in their surroundings, becoming part of the solution to problems. This research are expected to assist educators in discovering and determining new, more dynamic formulas in teaching and learning in schools such as concept, metode, approach, evaluation in teaching, and ultimately fostering learners' critical thinking abilities by prioritizing a deconstructive perspective.